Theories of International Politics and Zombies - DANIEL W. DREZNER (Princeton University Press, 2014)
Fifteen years ago, on a cross-country drive, I stopped to visit Graceland. By the time my tour hit the Jungle Room, it was obvious that the thirty-odd people walking through Elvis Presley’s mansion fell into two groups. The first contingent was thoroughly, utterly sincere in their devotion to all things Elvis. They were hardcore fans, and Graceland was their Mecca, their Jerusalem, and their Rome. Many of them sounded convinced that the King was still walking the earth. They gasped when they saw the jumpsuit collection, bedazzled by its grandeur. The second group of tourists was equally delighted to be at Graceland, but for a different reason. These people took great pleasure in the kitschy nature of all things Elvis. To them, a mansion that preserved the aesthetics of green shag carpeting and mirrored walls was both funny and tacky. They too gasped when they saw the jumpsuit collection, bedazzled by how ridiculous they thought it was. As we ambled along, the sheer professionalism of our tour guide struck me. Her task was not an easy one. She had to provide a veritable font of Elvis knowledge to all of the intense devotees. At the same time,she also had to acknowledge the absurdist nature of the experience for of the rest of the tour group.